A comparative assessment of performance and emission characteristics of a DI diesel engine fuelled with ternary blends of two higher alcohols with lemongrass oil biodiesel and diesel fuel. Issue 6 (September 2022) - Seeniappan, Kaliappan; Venkatesan, Balaji; Krishnan, Nithyanandan Navaneetha; Kandhasamy, Thanigavelmurugan; Arunachalam, Shanmugam; Seeta, Raghuram Kandregula; Depoures, Melvin Victor
Utilisation of high carbon alcohols in diesel engines as fuel is gaining importance among researchers because of its better fuel properties that are compatible with mineral diesel. The present study utilises two such alcohols namely octanol and decanol along with diesel and biodiesel derived from lemongrass. Two ternary blends, 50% by volume of diesel – 30% by volume of biodiesel – 20% by volume of octanol, and 50% by volume of diesel – 30% by volume of biodiesel – 20% by volume of decanol, were prepared, and different engine characteristics were analysed and compared with both neat diesel and biodiesel operation. Results indicated that peak cylinder pressure lowered with the ternary blend. Peak heat release rate was higher for octanol blend. When compared with octanol blend, 2.5% higher brake thermal efficiency was observed for decanol blend. However, still, the brake thermal efficiency was 3.5% lower than the diesel operation. The oxides of nitrogen emission for decanol blend were 4% lower than octanol blend. In general, smoke emission was lower for higher alcohol blends in comparison with the binary blend operation. Among the higher alcohol blends, octanol portrayed a 15% lower smoke opacity. Both the hydrocarbon emission and the carbon monoxide emission increased with higher alcohol blends. The study revealed that 1-decanol could be a potential fuel candidate for diesel engines operating with biomass-derived lemongrass oil biodiesel.